Intrapartum Care for People with Diabetes—Working towards Evidence-Based Management - Fishel Bartal, Michal (American Journal of Perinatology, 2024)
The consensus in the literature supports the need for careful monitoring and management of maternal blood glucose during labor to optimize neonatal outcomes. Guidelines generally recommend strict control of maternal blood glucose during labor, involving frequent checks, and the use of dextrose and insulin as needed. However, recent evidence has not consistently shown a strong association between strict control of blood glucose and a reduction in the rate of neonatal hypoglycemia. This raises questions about the extent to which intrapartum blood glucose control impacts neonatal hypoglycemia. This review aims to explore the literature on intrapartum maternal blood glucose management in individuals with pregestational or gestational diabetes, utilizing peer-reviewed journals and datasets, including PubMed, Google Scholar, and clinical guidelines. Observational studies, small sample sizes, variability in definitions of maternal hyperglycemia and neonatal hypoglycemia, and differences in measurement methods such as timing and thresholds for intervention limit the literature on this topic. Additionally, many studies may not fully account for confounding factors such as maternal body mass index, diet, and other comorbidities affecting blood glucose levels. These limitations underscore the need for a cautious interpretation of current findings and highlight the necessity for future research in this area. This review elaborates on the available data and summarizes evidence on managing labor in pregnancies complicated by diabetes. We also emphasize the need for further research to clarify the relationship between maternal blood glucose during labor and neonatal blood glucose.
Keywords: intrapartum; diabetes; neonatal hypoglycemia; insulin infusion; labor